Enhancing EFL Speaking Skill Through Student Mobility Program (Case of Non English Department Students) - Rahmawati, Amalia; Nur Syafiq, Ahmad; Anwari, Anwari; Isnina, Fathimah (Prosiding University Research Colloquium, 2021)
Internalization program especially student mobility program in campus is important not only to improve the quality of the campus but also to improve the students’ quality. By joining the program, the student can learn many thing, such as culture, all about SDGs, ect. The main thing of the student mobility program is the EFL has chance to practice their skill to speaking during the program. The program done virtually for 2 weeks. This research aims to describe the speaking improvement through student mobility program. This research belongs to pre-experimental design with pre-test and posttest. The population and sample is 10 students as the representative of Indonesia campus, and the sampling technique used is total sampling. The data was analysed statistically and provided the qualitative data to strength the research. There are five indicators that have been improved, such as pronunciation, grammar, vocabulary, fluency, and comprehension. It can be concluded that there is a significant different before and after joining student mobility program.